Banks’ Performance Amid the Unexpected Crises: An Assessment from Malaysia’s Islamic Banks - AHMAD, ZURIYATI; Yusof Ali, Noorhayati; Abdul Ghani, Roseziahazni (Information Management and Business Review, 2024)
Islamic banks play an important role in Malaysia’s financial system by offering various services to individuals, businesses, and governments. Nonetheless, as the world confronted unprecedented crises the Islamic banks faced a new set of tests that would not only define their performance but also underscore their adaptability and durability. This paper aims to evaluate the impact of unexpected crises on the performance of Islamic banks. It also delves into various Islamic bank’s key characteristics that might influence the Islamic bank performance such as capital adequacy, bank size, credit risk, and non-interest income. Data spanning from 2000 to 2022 and covering seven (7) Islamic banks are utilized using the panel static method. It reveals that bank characteristics such as capital adequacy, credit risk and non-interest income significantly impact Islamic bank performance. Nonetheless, deposit and bank size do not influence Islamic bank performance. The major highlight of the unexpected crises depicts a negative relationship with bank performance nonetheless it is not significant. This finding supports the claim that Islamic banks remain largely unaffected by unexpected crises. Therefore, a comprehensive understanding of these factors is crucial for policymakers, investors, and bank stakeholders to assess the health and performance of Islamic banks.